The role of diets and dietitians for para-athletes: A pilot study based on interviews - Yokoyama, H.; Deguchi, M.; Hongu, N. (Nutrients, 2022)
Efforts to provide nutrition support to para-athletes have not been established to date, and are far behind those established for athletes without disabilities. In the present study, we attempted to clarify the actual situation regarding dietary challenges of para-athletes. The aim of this study was to obtain clues to effective intervention methods that encourage the practice of sports nutrition. Six active elite para-athletes (30-70 years, four males) and a female physical therapist without physical disability participated in semi-structured interviews. All para-athletes had lower-limb disabilities and participated in the international wheelchair sports competitions (tennis, softball, and table tennis, with 2-26 years of player history). The interview items were on the ideal diet for improving competitive performance, evaluation of their typical diets, and the role of the dietitian as support. Responses obtained from participants were analyzed using quantitative content analysis by language analysis software. There are differences in the ideal diet based on the characteristics of the sport, but most participants believed that a nutritionally well-balanced diet with abundant vegetables was ideal for improving competitive performance. Para-athletes who use a wheelchair daily pay attention to their total calorie intake, because gaining weight is a critical issue for operating their wheelchairs and transferring themselves to and from their wheelchairs. Despite their world-class competition levels, none of them received routine dietary advice from dietitians. Some para-athletes did not even feel the need to engage with dietitians. Even for these para-athletes at a high level of competition, the "ideal diet" they considered was not always the optimal diet for improving their competitive performance. In addition, there are various barriers to practicing their optimal diet due to disability characteristics. Dietitians need to understand these barriers, their concerns and conflicts, and how to help them plan the optimal diet to improve their performance and maintain overall health.